Multigenerational Epigenetic Regulation of Allergic Diseases: Utilizing an Experimental Dust Mite-Induced Asthma Model - Pulczinski, Jairus C.; Shang, Yan; Dao, Tyna; Limjunyawong, Nathachit; Sun, Qinying; Mitzner, Wayne; Cheng, Robert YS; Tang, Wan-yee (Frontiers in Genetics, 2021)
Environmental exposures have been linked to increased asthma risk, particularly during pregnancy and in early life. Here we use a mouse model of allergic lung disease to examine the effects of pre- and perinatal house dust mite (HDM) allergen exposure on offspring phenotypic and transcriptional outcomes in three generations. We show that maternal HDM exposure (F0) acts synergistically with adult HDM exposure, leading to enhanced airway hyperresponsiveness (AHR) and lung inflammation when compared to mice exposed solely in adulthood. Additionally, a subset of F1 males were not challenged in adulthood, and used to generated F2 progeny, which was then used to generate F3 progeny. Upon adult challenge to HDM, F2 and F3 males generated from the maternal HDM (F0) exposure lineage displayed increased airway reactivity and inflammation when compared to mice exposed solely in adulthood. These findings indicate that maternal allergen exposure is capable of enhancing either susceptibly to or severity of allergic airway disease. To examine the role of epigenetic inheritance of asthma susceptibility induced by maternal HDM exposure, we utilized a genome-wide MeDIP-seq and hMeDIP-seq analysis to identify genes differentially methylated (DMG) and hydroxymethylated (DHG), and their association with the enhanced AHR. In addition, we validated the relationship between DNA methylation and mRNA expression of the DMGs and DHGs in the male sub-generations (F1-F3). We found the expression of Kchn1, Nron and Spag17 to be differentially hydroxymethylated, and upregulated in the F1 exposed to HDM both in early life and in adulthood when compared to F1 mice exposed solely in adulthood. Kcnh1 remained upregulated in the F2 and F3 from the maternal HDM (F0) exposure lineage, when compared to F1 mice exposed solely in adulthood. In summary, we demonstrated that maternal HDM exposure in early life can alter the gene expression and phenotype of offspring upon adult HDM exposure, resulting in more severe disease. These effects persist at least two generations past the initial insult, transmitted along the paternal line.